Financial Indicators as Predictors of UNDP’s Human Development Index (HDI): A Literature Review - Delgado, Christina Patricia; Japos, Genaro (JPAIR Multidisciplinary Research, 2023)
This paper presents a novel reinforcement of financial indicators as predictors of UNDP’s Human Development Index (HDI). The review focused on the roles of each financial index as a mediator of a positive relationship between the World Bank’s financial indicators and HDI. The literature review focused on how each financial indicator affects human development, whether the indicators significantly predict global HDI, and whether there was a significant relationship between the financial indicators and the 69 countries’ HDI. The study used content analysis of scientific sources generated through Google Bard, ChatGPT, and the Consensus app. The sources and references came from research databases such as Google Scholar, Scopus, Clarivate Analytics, and DOAJ. Results showed a significant correlation between financial indicators and human development. The study concluded that financial indices such as financial development, inclusion, and financial sustainability were significant predictors of human development.